High blood glucose level increase cardiovascular disease risk in type 2 diabetes mellitus - Marchelia, Laili Zahrina; Purwati, Purwati; Wironegoro, Rio (Folia Medica Indonesiana, 2017)
Type 2 diabetes mellitus (DM) is the 10th leading cause of death in the world and had a risk 4.06 times greater to have cardiovascular disease (CVD). Fasting plasma glucose and 2-hours postprandial glucose level as diagnostic tests to evaluate DM and also as a predictive factors to CVD. This research uses descriptive analytic research with cross sectional design. The subject of this study is Type 2 DM patients came to Dr Soetomo hospital from January-October 2014. Data was recorded from medical records of patients and was analyzed with Chi Square test with p<0.05. As result, there is 102 Type 2 DM patients with 36 patients have CVD manifestation and 66 patients without complication. There is a significant association between fasting plasma glucose (FPG), 2-hours postprandial glucose (2hPPG) level, and CVD manifestation (p=0.00). So FPG and 2hPPG have a significant association with CVD manifestation. There are other factors that influencing the formation of CVD, hence, further research is needed.